Genetic and environmental influences on beef cattle production in Zambia. 3. Carcass characteristics of purebred and reciprocally crossbred castrated males - Thorpe, W.R.; Cruickshank, D.K.R.; Thompson, R. (Cambridge University Press, 1980)
Carcass characters for 365 male castrated cattle of the Africander, Angoni, Barotse and Boran breeds, and the reciprocal crossbreds of the latter three were reported. In each of the two year-of-birth groups, different slaughter-age/management regimes were used. For all carcass characters except those related to size, the two Sanga breeds, Africander and Barotse, were very similar, as were the two zebu breeds, Angoni and Boran. The introduced breeds, Africander and Boran, which had similar carcass weights, had heavier carcasses (+18 kg, +10%) than the indigenous Barotse and Angoni breeds. The Sanga breed carcasses had less fat cover than those of the zebu breeds. Maternal effects were not important for carcass characters and the Angoni/Barotse and Angoni/Boran crosses showed no heterosis. In the Barotse/Boran crosses, slaughter and carcass weights and eye muscle area gave between 8% and 9.5 heterosis, and the linear carcass measurement between 2% and 3%. There was no economic advantage in delaying slaughter to the later of the two ages compared in the two year-of-birth groups.